2005
DOI: 10.1021/ja051107v
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Homopolymer as a Reaction Medium in Water:  Product Selectivity within Polymeric Nanopockets

Abstract: A styrene-based water-soluble polymer has been explored for its use as a host for lipophilic substrates in aqueous medium. Unimolecular reactions, namely, photo-Fries rearrangement of naphthyl esters, alpha-cleavage reaction of 1-phenyl-3-p-tolyl-propan-2-one, and Norrish type I and type II reactions of benzoin alkyl ethers were examined. We find that the hydrophobic domains generated by the polymer not only restrict the mobility of the radicals but also modestly incarcerate the substrate, intermediates, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 49 publications
1
66
0
1
Order By: Relevance
“…[26,27] A further advantage of polymeric self-assembled systems is their stability over surfactant-based micelles, creating a more "protected" kinetically frozen pocket within the core domain. [27][28][29] Moreover, by covalently attaching the catalytic functionality within the polymer backbone, it can be easily recovered after reaction by precipitation or ultrafiltration methods. [30,31] Therefore, polymeric core-shell-type catalytic nanoreactors have been investigated in which the hydrophobic core provides a favorable confined environment for the hydrophobic starting materials, while the hydrophilic shell guarantees water solubility.…”
Section: Well-defined Polymeric Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[26,27] A further advantage of polymeric self-assembled systems is their stability over surfactant-based micelles, creating a more "protected" kinetically frozen pocket within the core domain. [27][28][29] Moreover, by covalently attaching the catalytic functionality within the polymer backbone, it can be easily recovered after reaction by precipitation or ultrafiltration methods. [30,31] Therefore, polymeric core-shell-type catalytic nanoreactors have been investigated in which the hydrophobic core provides a favorable confined environment for the hydrophobic starting materials, while the hydrophilic shell guarantees water solubility.…”
Section: Well-defined Polymeric Nanostructuresmentioning
confidence: 99%
“…3). [29] Their studies revealed that the hydrophobic domains created by a kinetically frozen styrenic-based amphiphilic homopolymer stops hydrolysis of hydrophobic substrates and offers better selectivity control than micelles formed from small molecule surfactants. This is due to the more stable and confined hydrophobic pocket generated by the amphiphilic homopolymer compared with that for small molecule surfactants.…”
Section: Well-defined Polymeric Nanostructuresmentioning
confidence: 99%
“…For example, polystyrene-poly(ethylene glycol) (PS-PEG) has been often used for catalyst support and applied to organic reaction in water because they construct effective catalytic sites with high affinity to both hydrophobic and hydrophilic reagents. [103][104][105][106][107][108][109][110][111][112][113][114][115] On the other hand, an assembled complex (2) of a noncross-linked copolymer of PNIPAAm with an ammonium ion and phosphotungstic acid (H 3 PW 12 O 40 ), which is insoluble in water, works as an efficient oxidation catalyst under organic solventfree conditions, such as in water. [116][117][118] When a series of epoxidations of several allylic alcohols with hydrogen peroxide was performed in the presence of 2, hydrophobic substrates were converted to the corresponding epoxides in high yields under an organic solvent-free triphasic system, and recovered 2 can be used for consecutive reactions (Scheme 6).…”
Section: Organic Solvent-free Triphase Oxidation Catalysismentioning
confidence: 99%
“…Recently, micelles have attracted great interest in biological applications including drug delivery, [1] reaction mediates, [2] hydrolysis enzyme models, [3] and chemosensors. [4] For example, Gröger et al have demonstrated that miniemulsions can act as efficient 'nanoreactors' to catalyze enantioselective enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%